2004
DOI: 10.4065/79.11.1444
|View full text |Cite
|
Sign up to set email alerts
|

Life-Threatening Serotonin Syndrome in a Patient With Chronic Heart Failure and CYP2D6*1/*5

Abstract: We report a case of serotonin syndrome that occurred in a patient with chronic heart failure associated with a panic disorder. The 39-year-old Japanese man had been treated with paroxetine at 20 mg/d for 1 1/2 years. He presented with rhabdomyolysis, renal failure, fulminant liver failure, cardiac conduction disturbance, and disseminated intravascular coagulation, as well as conventional symptoms of serotonin syndrome including alterations in cognition (disorientation, confusion) and behavior (restlessness), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…11,12 Shivering has been implicated, but shiveringassociated muscle damage has been more commonly seen in hyperthermic syndromes such as malignant hyperthermia, neuroleptic malignant syndrome, and serotonin syndrome. 11,13 We believe that this person's rhabdomyolysis was likely caused by deoxygenated blood in the lower limbs secondary to being passively suspended in a harness for a prolonged time. Rhabdomyolysis has been described in other victims immobilized on rope.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…11,12 Shivering has been implicated, but shiveringassociated muscle damage has been more commonly seen in hyperthermic syndromes such as malignant hyperthermia, neuroleptic malignant syndrome, and serotonin syndrome. 11,13 We believe that this person's rhabdomyolysis was likely caused by deoxygenated blood in the lower limbs secondary to being passively suspended in a harness for a prolonged time. Rhabdomyolysis has been described in other victims immobilized on rope.…”
Section: Discussionmentioning
confidence: 98%
“…11,12 Shivering has been implicated, but shivering-associated muscle damage has been more commonly seen in hyperthermic syndromes such as malignant hyperthermia, neuroleptic malignant syndrome, and serotonin syndrome. 11,13…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies suggest a key role of the immune system in the development of ticlopidineinduced liver damage (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Few results from [11][12][13][14] N/A N/A N/A past research suspected the contribution of cytochrome P450 enzyme system variability to drug-induced hepatotoxicity (28)(29). The genetic polymorphism of certain cytochrome P450 enzymes lead to differences in actual drug metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic polymorphism of certain cytochrome P450 enzymes lead to differences in actual drug metabolism. The evidence from published studies showed that "slow metabolizers" have increased susceptibility to drug-induced toxicity (11,(28)(29). We aimed to investigate the role of cytochrome CYP2C 19 genetic polymorphism in the development of ticlopidineinduced cholestatic hepatitis and relate it to the specific immune reactivity and the inducement of necrosis and apoptosis as possible mechanisms of liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously by Alderman et al, 42 a single-point pharmacokinetic study by Nichols et al 43 found that when treated with paroxetine, healthy controls had a 419% increase in the CYP2D6 substrate desipramine AUC and a 90% increase in peak plasma concentration in comparison to desipramine substrate alone. Sato et al 44 described a case of serotonin syndrome treated with paroxetine at 20 mg/d. The plasma concentration of paroxetine was substantially elevated (70 ng/mL; reference range, <23 ng/ mL), which was attributed in part to the patient's CYP2D6 genotype of intermediate metabolizer.…”
Section: Pharmacogeneticsmentioning
confidence: 99%